Juridical Analysis of The Application of The Principle of Good Corporate Governance in Enterprises Owned By Batu Beriga Village, Central Bangka Regency As A Village-Based Business Entity - Maulana; Rahmiati Ranti Pawari (Ekasakti Jurnal Penelitian dan Pengabdian, 2026)
Village Owned Enterprises (BUMDes) are strategic instruments in village economic development which are expected to be able to improve community welfare through professional management of local potential. Strengthening the position of BUMDes as a legal entity through Government Regulation Number 11 of 2021 emphasizes the importance of good governance in achieving these goals. However, in practice, there is still a gap between normative goals and empirical implementation, especially related to the effectiveness of the management and implementation of the principles of Good Corporate Governance (GCG) at the village level. This study aims to analyze the implementation of BUMDes Batu Beriga in achieving the goals as stipulated in Government Regulation No. 11 of 2021 and examine the application of GCG principles in its management. The research method used is empirical juridical with a legislative approach and a case approach. Data was obtained through document studies and interviews, then analyzed qualitatively using descriptive-analytical techniques. The results of the study show that formally the Batu Beriga BUMDes have fulfilled the aspect of institutional legality, but substantively it has not been optimal in achieving the goal of increasing Village Original Income and community economic empowerment. The application of GCG principles has also not been running optimally, especially in the aspects of transparency, accountability, and independence which are still influenced by limited managerial capacity and dominance of local actors. The implications of this study confirm that the success of BUMDes is not only determined by legal legitimacy, but also by the quality of good governance. Therefore, it is necessary to strengthen institutional capacity, improve the professionalism of managers, and have effective supervision mechanisms to encourage the optimal application of GCG principles to achieve the goals of sustainable village economic development.